2008
DOI: 10.1517/14740338.7.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death secondary to antidepressant and antipsychotic drugs

Abstract: A number of antipsychotic and antidepressant drugs are known to increase the risk of ventricular arrhythmias and sudden cardiac death. Based largely on a concern over QT prolongation and the development of life-threatening arrhythmias, a number of antipsychotic drugs have been temporarily or permanently withdrawn from the market or their use restricted. Some antidepressants and antipsychotics have been linked to QT prolongation and the development of Torsade de pointes arrhythmias, whereas others have been ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 120 publications
2
57
0
4
Order By: Relevance
“…1,3 In a study of 98 patients experiencing an overdose of tricyclic antidepressants, Goldgran-Toledano et al 18 reported that overall mortality among all patients was 3%, but among patients who displayed a Brugada phenotype it was 6.7%. Rouleau et al 3 reported 3 cases of psychotropic drug-induced Brugada ECG, occurring during coadministration of amitriptyline and other antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 In a study of 98 patients experiencing an overdose of tricyclic antidepressants, Goldgran-Toledano et al 18 reported that overall mortality among all patients was 3%, but among patients who displayed a Brugada phenotype it was 6.7%. Rouleau et al 3 reported 3 cases of psychotropic drug-induced Brugada ECG, occurring during coadministration of amitriptyline and other antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Amitriptyline, a widely used tricyclic antidepressant, has been reported to induce an ST segment elevation in the right precordial leads (V1-V3) of the electrocardiogram (ECG) consistent with the Brugada syndrome (BrS), thus unmasking BrS. 2,3 BrS is an inherited cardiac disorder associated with a high incidence of sudden death due to the development of life-threatening polymorphic VT and VF.…”
Section: Introductionmentioning
confidence: 99%
“…Bradycardia (heart rate (HR) <60 bpm) is one of the most common symptoms seen in patients with AN (FC <40 bpm is a criterion for hospital admission) [21]; it is a consequence of the reduction of the basal metabolism and of the vagal hypertone; also bradycardia is an adaptive phenomenon to protein-energy malnutrition, allowing, through a reduction in cardiac output, to reduce energy expenditure. Therefore a normal or increased CF, in cases of moderate-severe AN, may be indicative of clinical risk [22].…”
Section: Cardiovascular Alterations In Eating Disordersmentioning
confidence: 99%
“…Ventricular dysrhythmias, including ventricular tachycardia (VT), torsade de pointes (TdP) and ventricular fibrillation (VF), have been reported in association with therapeutic use of or overdose by a number of drugs, most commonly antidepressant and antipsychotic agents [1][2][3][4][5]. Published clinical experience regarding ventricular arrhythmias and TdP in drug overdose is derived primarily from single case reports or small case series [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%